A case study of an English as a foreign language student focused on writing skills - TEFL program portfolio - Heredia Quinde, Tania Mireya (2012)
English is an important tool to communicate with others. However, it’s teaching-learning process, as a foreign language, is not easy. The problem researched in this case study is focused on writing. This study was conducted with Sebastian, a 14 year old student who was evaluated before the tutorial was conducted and it was found that Sebastian’s native language: Spanish, was sometimes a reason for his writing errors. That is why the necessity to strengthen these skills was shown and therefore exercises and assignments were conducted to improve his performance in these aspects. The 6 traits of writing pioneered by Education Northwest were used as a base for this study where the application of mixed methods helped to avoid subjective appreciations on the student’s work. The 6 traits of writing helped with the quantitative evaluation while the teacher’s abilities supported the qualitative information. Also, since in the teaching process it is important to think about the mentor’s practice, the TEFL’s portfolio aim was to analyze the educational research done in order to identify weaknesses and propose improvements for future studies.